Logo and Packaging Design as Promotion Media and Visual Identity for Azzahra Kemojo Duri’s MSME - Hardinata, Niky; Asra, Yunelly; Nosa, Muhammad Ridho; Triyono, Wahyu (Inovbiz: Jurnal Inovasi Bisnis, 2023)
Azzahra Kemojo Duri is one of the MSMEs located in Duri, Mandau sub-district, Bengkalis district, Riau province which is engaged in the culinary field, specifically producing Kemojo cakes. Along the way, Azzahra Kemojo Duri’s MSME had difficulties in increasing its production value due to one of the factors regarding visual identity which was not well known to the public. Through needs analysis, it was found that so far Azzahra Kemojo Duri did not have a specific design concept, so consumers are more familiar with the owner's name than the visual brand name. Therefore, it is necessary to design a visual identity design by applying the design thinking method. The use of the design thinking method in this study aims to collect and manage data systematically to produce logos and packaging designs that are attractive and appropriate for use. The results of designing this visual identity are in accordance with what is needed by MSMEs, namely in the form of logos and product packaging. The result of further application of the logo design is that it can be applied in the form of stickers designs and also flyer